Kinematic analysis with motion sensors in kayakers: A study with boyacense athletes - Callejas-Cuervo, M.; Pacanchique-Florez, V. M.; Sanabria-Arguello, Y. D. (Journal of Human Sport & Exercise, 2021)
Objective: The results of the stroke cycle kinematic analysis of a group of kayakers from a city of Colombia are presented, using a motion capture platform based on inertial and magnetic sensors. Method: Quantitative approach of a cross-sectional descriptive type. A group participated with similar anthropometric characteristics such as size, mass, and body mass index. A technological platform was used that allowed the measurement of the kinematics of their movements from the first stroke cycle until the end at a 200-metre distance. Results: With the use of inertial and magnetic sensors, a comparative study of the kayakers of the sample was carried out, verifying that the distance reached by the boat in every stroke is greater on the right side with a distance of 3.651 metres and the minimum on the left side with a distance of 0.762 centimetres. The smaller amount of strokes that were made in the 200-meter test was 81 strokes/minute and the best displacement average was 2.387 meters, data that allow the measurement of the speed, displacement of the boat and number of strokes, are the most important factors to obtain better marks in this sport discipline. Conclusions: The lack of preparation of the kayakers was demonstrated since the stroke cycle in the aerial and aquatic phases is deficient, as the paddle blade does not enter the water in its maximum amplitude and the fluctuation in the control of the rate are factors that generate a smaller displacement of the boat.